HUBUNGAN DUKUNGAN KELUARGA DENGAN KEJADIAN DEPRESI PADA PASIEN KANKER PAYUDARA YANG MENJALANI KEMOTERAPI - Erni ' Kartika; Gamya Tri Utami; Arneliwati ' ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Breast cancer patients who undergoing chemotherapy may lead to the occurence of depression. Family approach is  needed to containment procedured of depression, by provided support to patients This research was conducted to determine the relationship between family support with the incidence of depression in breast cancer patients undergoing chemotherapy. This research used descriptive correlation design with cross sectional approach. This research was conducted in Anyelir room at Arifin Achmad Hospital Riau Province on 42 samples and taken by purposive sampling techniques which selected based on inclusion criteria. Measuring instruments was form of questionnaire already been tested for validity and reliability. The analysis was bivariate analysis using Chi-Square. The results showed there was correlation between family support with the incidence of depression in breast cancer patients undergoing chemotherapy with ρ value (0.002) < α (0.05). Based on these results, the family was expected to provide support to breast cancer patients who undergoing chemotherapy that can help lower the incidence of depression in undergoing chemotherapy. Keywords: Breast cancer, family support, insidince of depression